Evaluation of an enhanced game based learning framework through VLE / Lai Ngan Kuen - Lai , Ngan Kuen (2018)
The effectiveness of an education system is highly dependent on the teaching and learning approaches used. The conventional ways of teaching and learning are no longer sufficient to ensure quality of education as well as engage students’ interest in learning, especially in this digital era. Various research have focused on creating effective teaching and learning environments to enhance the traditional approach. Game-based learning (GBL) utilises the gaming environment to attract the student's attention and increase participation throughout the process of learning. Although GBL has been present in the Malaysian preschool curriculum since the last decade, GBL is still not being practiced in the formal education system in Malaysia. The factors that have caused low adoption of GBL in Malaysia include the limitations of existing GBL frameworks, barriers to teacher’s adoption of GBL and issues regarding transfer of knowledge. To study and counteract against these challenges, this research proposes a GBL framework that focuses on the development of language and communication, cognitive, and psychomotor skills for preschool children. A learning system using virtual learning environment (VLE) was designed to evaluate the effectiveness of the proposed framework in promoting learning for preschool children. Two surveys were used to identify the scope of the syllabus for the proposed learning system and to gauge its usefulness in achieving research objectives. 84 preschool children participated in this study. Their learning performances were evaluated through a quasi-experimental approach. The results show that learning performance improved significantly, and moreover, the learning system increases the teacher’s willingness to adopt GBL for preschool children.